Structural validity of the foot and ankle outcome score for orthopaedic pathologies with Rasch Measurement Theory. Issue 2 (February 2022) - Tapaninaho, Krista; Saarinen, Antti J.; Ilves, Outi; Uimonen, Mikko M.; Häkkinen, Arja H.; Sandelin, Henrik; Repo, Jussi P.
Highlights: Foot and Ankle Outcome Score is one of the most reported patient-reported outcome score. There is a notable variance in reliability and validity in the outcome measures. Rasch analysis is used for assessing the structural validity and dimensionality. FAOS was found to have acceptable structural validity for assessing orthopedic foot and ankle conditions. Abstract: Background: The Foot and Ankle Outcome Score (FAOS) is one of the most frequently used patient-reported outcome measures for foot and ankle conditions. The aim is to test the structural validity of the Finnish version of the FAOS using Rasch Measurement Theory. Methods: FAOS scores were obtained from 218 consecutive patients who received operative treatment for foot and ankle conditions. The FAOS data were fitted into the Rasch model and person separation index (PSI) calculated. Results: All the five subscales provided good coverage and targeting. Three subscales presented unidimensional structure. Thirty-eight of the 42 items had ordered response category thresholds. Three of the 42 items had differential item functioning towards gender. All subscales showed sufficient fit to the Rasch model. PSI ranged from 0.73 to 0.94 for the subscales. Conclusions: The Finnish version of the FAOS shows acceptable structural validity for assessing complaints in orthopaedic foot and ankle patients.